A Comparative Assessment of Uncrushed-River Concrete Mix of Hari-River, and Kamar-Kalaq: the Two Widely Used Concrete Mix in Herat, Afghanistan - Alkozay, Arif; Amanollah Faqiri; Noman Moheb; Khalid Ahmad Ahmadi; Sayed Naqibullah Sadat; Mohammad Yaser Saddeqi; Ahmad Fawad Jamshidi; Mir Mohammad rateb Sayedi; Safiullah Mohammadi (International Journal of Integrated Science and Technology, 2024)
Concrete, as a cornerstone of modern construction, heavily relies on the quality of its constituent materials, particularly aggregates. This study delves into a comparative analysis of aggregates sourced from two widely utilized riverbed regions, namely Hari-River and Kamar-Kalaq, situated within Herat province, Afghanistan. Given that over 90% of concrete in Herat province is sourced from these two riverbeds, the findings of this study carry immense significance. The research meticulously examines key parameters, including clay content, gradation, aggregate shape, and compressive strength, to determine the optimal choice for concrete production. Methodologically, samples were acquired following ASTM standards, and rigorous testing procedures were conducted, encompassing clay particle analysis, sieve analysis, and strength testing. The results reveal significant disparities between the two regions, with Hari-River demonstrating superior characteristics across various metrics. Particularly noteworthy is Hari-River's lower clay content, superior gradation, and higher compressive strength compared to Kamar-Kalaq.